Backstage at a movie set - Wessling, Katherine (New York Children's Press, 2003)
Explores the history of motion picture production, key players in the process of making a film, a typical day of shooting, and how to pursue one's interest in the field, either as a career or as a hobby
The wonderful world of movies -- Ready for action -- We're rolling! -- Breaking in
American Corner
Includes bibliographical references (p. 44) and index
11
Keywords: Cinematography -- Juvenile literature; Cinematography; Motion pictures -- Production and direction -- Juvenile literature; Motion pictures -- Production and direction